2018
DOI: 10.1073/pnas.1720520115
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Staphylococcus aureus virulence by a small-molecule compound

Abstract: Emerging antibiotic resistance among bacterial pathogens has necessitated the development of alternative approaches to combat drug-resistance-associated infection. The abolition of virulence by targeting multiple-virulence gene products represents a promising strategy for exploration. A multiplex promoter reporter platform using- dual-reporter plasmids with selected promoters from -virulence-associated genes was used to identify compounds that modulate the expression of virulence factors. One small-molecule co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 41 publications
0
50
0
1
Order By: Relevance
“…A growing number of studies highlight the therapeutic potential of targeting ClpP. A recent study describes a selective, small-molecule inhibitor of ClpP, identified via high-throughput screening and which attenuates virulence in mouse models of S. aureus USA300 infection (55). Our work and others suggest therapeutically targeting ClpP may have great promise in treating invasive S. aureus infections.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies highlight the therapeutic potential of targeting ClpP. A recent study describes a selective, small-molecule inhibitor of ClpP, identified via high-throughput screening and which attenuates virulence in mouse models of S. aureus USA300 infection (55). Our work and others suggest therapeutically targeting ClpP may have great promise in treating invasive S. aureus infections.…”
Section: Discussionmentioning
confidence: 99%
“…aureus UAMS-1 [59], it is possible that CodY negatively regulates urease gene transcription through repressing Agr, since the agrA gene encoding the Agr response regulator is upregulated in the UAMS-1 ΔcodY mutant [59]. More in-depth future studies are required regarding the regulation of urease, as other transcriptional regulators such as Sae [60, 61], ClpP [6264], and MgrA [65], are suggested to contribute to the regulatory network that fine-tunes urease activity. Lastly, it is interesting that CcpA activates ure transcription but represses rocF (arginase) transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Within this complex, ClpX 6 recognizes and unfolds substrate proteins for subsequent digestion by ClpP 14 . Previous research identified various small‐molecule inhibitors of ClpP . Among those, reversible oxazole compounds displayed excellent potency on the ClpP peptidase but suffered from a ClpX‐mediated repulsion based on conformational selection, thus preventing inhibition of ClpXP .…”
Section: Figurementioning
confidence: 99%